(untitled) (Journal of School Administration Research and Development, 2020)
This essay details ways in which curriculum leaders can critically engage with contemporary needs to produce a “becoming-curriculum”—with lines of flight breaking free from prescriptive, reductive triangulations—by opening curriculum to present and future (rather than past) realities. Evolutionary theory, the work of Deleuze and Guattari, and culturally responsive leadership can help to reconceptualize curriculum studies and community-based education. As we prepare students for an unknowable future, how can we better care for the actual students and communities in front of us rather than the potential lives of abstract, future adults?